Politik Hukum Pidana Pasal 240 Ayat (1) Huruf G Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum Terkait Membolehkan Eks Narapidana Korupsi Untuk Mencalonkan Legislatif Dilihat Dari Undang-Undang Nomor 12 Tahun 2011 Tentang Pembentukan Peraturan Perundang-Undangan - Ferdricka Nggeboe; Reza Iswanto (Wajah Hukum, 2019)
The purpose of establishing a law is to protect the interests of society in general, not protect one's own interests. Therefore, in the content of Article 240 Paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections relating to allowing corrupt prisoners to nominate a legislative is very unfortunate because in Article 240 Paragraph (1) letter g of Law Number 7 years The 2017 General Election opens opportunities for ex-convicts to run for legislative membership, while the Indonesian state expects a government that is clean from corruption, collusion and nepotism. Criminal law politics Article 240 Paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections in relation to allowing ex-convicts to nominate legislative views of Law Number 12 of 2011 concerning Formation of Legislation Regulations is the contents of the contents of Article 240 Paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections is not appropriate because it contradicts Law Number 23 of 1999 concerning the Administration of a State that is Clean and Free of Corruption. The consequences if Article 240 Paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections is enacted is to facilitate ex-convicts of corruption to repeat their acts of corruption in government, cause public distrust of the government and complicate the Corruption Eradication Commission (KPK) in investigating criminal acts of corruption in the legislative body. Future criminal law politics in criminal law politics Article 240 Paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections in relation to allowing ex-convicts to nominate a legislature is that the Article should not be used anymore because there are still many people who have not been caught in sanctions criminal who wants to run for legislative candidates and provide opportunities for ex-convicts to do the action again. To get the results of this study, a normative legal approach is used by prioritizing library materials or secondary data which is carried out by analyzing Article 240 Paragraph (1) letter g of Law Number 7 of 2017 concerning General Elections and then related to expert opinion.